Pharmacists refuse to fill emergency contraception prescriptions. - Fielder, J.H (IEEE Engineering in medicine and biology magazine)
One of the many troubling aspects of the increased political activity by conservative Christians is the growing number of pharmacists who are refusing to fill prescriptions for Plan B, the emergency contraceptive. Taken within 72 hours of unprotected intercourse, Plan B is safe and effective in preventing pregnancy. Pharmacists who do this claim a right of conscientious objection, but women's groups and others see it as an attempt to enforce religious beliefs on patients who are in need. In this essay, the roots and history of the controversy, arguments both for and against, and a solution that provides a reasonable balance among the conflicting ethical issues are discussed.